Wander Alone: Study of Psychological Well-Being and Loneliness of Students with Disabilities: [Merantau Sendiri: Studi Kesejahteraan Psikologis dan Kesepian Mahasiswa Difabel] - Andriani, Gresia; Huwae, Arthur (ANIMA Indonesian Psychological Journal, 2024)
“Wandering” is a form of exploring education for every individual, especially when they want to enter higher education. Becoming a student wanderer, especially for students with disabilities is a challenge for every individual because of various problems that affect individual loneliness. This is inseparable to psychological well-being, and therefore, this study aims to determine the relationship between psychological well-being and loneliness of student wanderers with disabilities. The study method is quantitative with correlational design. A total of 76 student wanderers with disabilities who studied at Universitas Brawijaya were recruited as study participants utilizing total sampling. Measurements utilized the Ryff’s Scales of Psychological Well-Being (α = .923) and the Revised University of California, Los Angeles (R-UCLA) Loneliness Scale Version 3 (α = .848). Study results prove that psychological well-being is correlated with the loneliness of student wanderers with disabilities (r = - .452; sig. = .000; p < .01), indicating that psychological well-being is one of the factors related to loneliness in student wanderers with disabilities. Merantau menjadi salah satu bentuk pengeksplorasian pendidikan bagi tiap individu secara khusus ketika hendak masuk perguruan tinggi. Menjadi mahasiswa yang merantau, terlebih bagi mahasiswa difabel, merupakan tantangan tersendiri bagi tiap individu karena berbagai permasalahan yang berdampak pada kesepian individu. Hal ini tidak terlepas dari kesejahteraan psikologis, dan maka dari itu itu, studi ini bertujuan untuk mengetahui hubungan kesejahteraan psikologis dan kesepian mahasiswa difabel yang merantau. Metode studi adalah kuantitatif dengan desain korelasional. Sebanyak 76 mahasiswa difabel yang merantau dan berkuliah di Universitas Brawijaya dijadikan sebagai partisipan studi dengan total sampling. Pengukuran variabel menggunakan Ryff’s Scales of Psychological Well-Being (α = 0,923) dan Revised University of California, Los Angeles (R-UCLA) Loneliness Scale Version 3 (α = 0,848). Hasil studi membuktikan bahwa kesejahteraan psikologis berkorelasi dengan kesepian mahasiswa difabel yang merantau (r = - 0,452; sig. = 0,000; p < 0,01), mengindikasikan bahwa kesejahteraan psikologis menjadi salah satu faktor yang berhubungan dengan kesepian pada mahasiswa difabel yang merantau.